Nursing students’ attitudes toward cross-gender care: a cross-sectional study - Saumya P. Srivastava; Soni Chauhan; Anuj Singh; Surya Kant Tiwari; Surat Ram Kudi; Anchal Gupta (BMC Research Notes)
Abstract Objectives This study aimed to assess nursing students’ attitudes toward providing cross-gender care and to identify the factors influencing these attitudes. Results A cross-sectional study of 338 nursing students in Northern India found that over half (50.9%) had unfavorable attitudes towards cross-gender care. Female students demonstrated significantly more positive attitudes than male students (p < 0.01). Multiple regression analysis identified gender (β = 0.246, p < 0.001), academic year (β=-0.150, p = 0.009), and prior experience with cross-gender care (β = 0.100, p = 0.048) as significant predictors of attitudes. The regression model explained 19.9% of the variance in attitudes (R²=0.199, p < 0.001). Male students expressed concerns about providing quality physical care and emotional support for patients and felt inadequately prepared to provide physical and emotional support to opposite-gender patients. These findings highlight the need for enhanced gender-sensitive training in nursing education to improve attitudes and competencies in cross-gender care provision.